Addition of small‐bowel transit scintigraphy to gastric emptying for assessment of patients with upper gastrointestinal symptoms. Issue 2 (29th September 2020) - Maurer, Alan H.; Yu, Daohai; Lu, Xiaoning; Dadparvar, Simindokht; Kamat, Bhishak H.; Shahsavari, Dariush; Parkman, Henry P.
Abstract: Background: Dyspeptic symptoms are not well correlated with gastric emptying (GE) results. Aims: To determine (a) prevalence of delayed SB transit (SBT) in patients undergoing GE scintigraphy for symptoms of gastroparesis; (b) symptoms associated with delayed SBT. Methods: Patients with symptoms of gastroparesis underwent combined GE and SBT scintigraphy (GES/SBTS). Patients ingested a mixed solid (S)‐liquid (L) meal with egg whites labeled with 500 µCi Tc‐99 m sulfur colloid and water with 125 µCi In‐111 DTPA. Retained S and L gastric activity and percent of L In‐111 activity in terminal ileum (TI) and/or cecum/colon at 6 h were determined. Patient Assessment of Gastrointestinal Symptoms (PAGI‐SYM) assessed symptoms from 0 (none) to 5 (very severe). Key Results: Of 363 patients, 174 (47.9%) had delayed S GE, 141 (38.8%) delayed L GE, and 70 (19.3%) delayed SBT. Delayed SBT was seen in 24 (6.6%) with normal S GE and 46 (12.7%) with delayed S GE. Patients with isolated delayed SBT had highest symptom scores for postprandial fullness (3.5), stomach fullness (3.4), nausea (3.2), bloating (3.2), compared to isolated delayed S GE who had highest symptom scores for postprandial fullness (3.7), nausea (3.6), stomach fullness (3.4), and early satiety (3.3). Conclusions & Inferences: Delayed SBT occurred in 19.3% of dyspeptic patients using GES/SBTS. While postprandial and stomach fullness were common to both delayed S GE and delayed SBT, early satiety was associated with delayed S GE whereas bloating was associated with delayed SBT. Thus, SBTS can augment GES to help explain some symptoms associated with dyspepsia and suspected gastroparesis.